Pengembangan Materi Pendidikan Agama Islam Madrasah Ibtidaiyah Perspektif Integrasi Interkoneksi - Mujahada, Kharis Syuhud; Noviyandri, Hanifah (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
The dichotomous view of science infiltrates all directions and is no exception in the science of education. As a result of this dichotomy, knowledge is produced by individuals with double moral standards, for example, a Muslim who is devout in worship but at other times also corrupts, oppresses, and commits despicable acts. Normatively, in Islam, there is no dichotomy of knowledge even though, in reality, science dichotomy still occurs in Islamic education. To dismiss or eliminate this dichotomy, it is essential to have interconnection integration in the scientific structure, including in the development of Islamic Religious Education (PAI) material in Madrasah Ibtidaiyah (MI). This research is literature research with a descriptive approach. The development of PAI MI integration-Interconnection perspective material is classified into two, namely internal and external. Internally it is done by integrating or finding common ground between subjects in the PAI family. There are five subjects in the PAI family, namely; Qur'an, Aqeedah, Morals, Fiqh, and Date. The purpose of this internal interconnection integration is to help students get an integrated understanding of the five subjects. While externally, interconnection is carried out between material in the PAI family and article in science subjects. With these external interconnections, the truth of the revelations contained in PAI is expected to be supported by scientific reviews contained in Science / Natural Sciences material.